Effects of Low-Dose Ketamine on the Antidepressant Efficacy and Suicidal Ideations in Patients Undergoing Electroconvulsive Therapy. Issue 1 (March 2020) - Chen, Qibin; Dong, Jun; Luo, Jie; Ren, Li; Min, Su; Hao, Xuechao; Luo, Qinghua; Chen, Jianmei; Li, Xiao
Abstract : Objectives: It remains controversial whether a subanesthetic dose of ketamine could modulate the antidepressant effect of electroconvulsive therapy (ECT) in patients with major depressive disorder. We investigated the effect of ketamine on accelerating the antidepressant efficacy of ECT. Methods: One hundred twenty-seven patients with major depressive disorder were included in this randomized, placebo-controlled, double-blind study. The study group received 0.3 mg/kg ketamine, and the control group received an isovolumetric dose of normal saline before undergoing ECT under propofol anesthesia. The main outcome was the Hamilton Depression Rating Scale score after each ECT session. Suicidal ideation (SI) was also evaluated using the Hamilton Depression Rating Scale. The response, remission, and recurrence rates were analyzed using time-to-event analysis. Results: No significant differences were found in the overall response, remission, and relapse rates between the groups ( P > 0.05). The median number of ECT sessions for achieving response was 4.0 ± 0.41 in the study group and 7.0 ± 0.79 in the control group ( P < 0.05). The median number of ECT sessions for achieving remission in the study and control groups was 8.0 ± 0.29 and 9.0 ± 0.48, respectively ( P < 0.05). The median number of ECT sessions for achieving SI reduction in the study and control groups was 3.0 ± 0.75 and 6.0 ± 1.19, respectively ( P < 0.05). Conclusions: Low-dose ketamine (0.3 mg/kg) could modulate the antidepressant efficacy of ECT via accelerating the onset of its effects and reducing the number of ECT sessions required to obtain response, remission, and SI reduction, without influencing the relapse rates in remitting patients after ECT treatment.